2008
DOI: 10.1007/s11547-008-0325-y
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of multidetector-row CT with multiplanar reformation in guiding percutaneous lung biopsies

Abstract: MDCT MPR images allowed sampling of pulmonary lesions until now considered unreachable with axial MDCT guidance because of overlying bony structures (ribs, sternum and scapulae) or critical location (hilar-mediastinal, proximity to the heart or large vessels). Compared with the conventional procedure, the use of MPR images does not increase the rate of pneumothorax or the procedure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
0
15
0
3
Order By: Relevance
“…It has been recently demonstrated that using MPR, CT enables us to guide the needle to areas that cannot be reached with axial CT images [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been recently demonstrated that using MPR, CT enables us to guide the needle to areas that cannot be reached with axial CT images [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The images were processed with MRP along the needle axis to evaluate the needle path and its inclination in the three spatial planes [12,13,19].…”
Section: Ct-guided Fna Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is not infrequent for some lesions to be obscured by skeletal segments, abdominal organs, vessels and nervous structures so that MDCT-guided biopsy may also prove difficult, if not impossible. The introduction of MDCT has, however, allowed multiplanar reconstructions (MPR) to be obtained that have been shown particularly useful in guiding percutaneous pulmonary biopsies [14][15][16][17] The purpose of this paper is to illustrate the utility and advantages of MDCT with MPR in guiding FNAB and core Parole chiave Tomografia coomputerizzata · Biopsia · Retroperitoneo · Tumori Introduzione L'agoaspirazione con ago sottile (FNAB) e l'agobiopsia, eseguite con approccio percutaneo, sono procedure scarsamente invasive e di provata sicurezza ed efficacia, spesso impiegate nella definizione cito-istologica di lesioni retroperitoneali nelle quali l'imaging non è stato in grado di fornire una diagnosi di certezza [1,2]. L'esame cito-istologico è di fondamentale importanza nella diagnosi di natura, ma anche nella fase di stadiazione della neoplasia, nell'impostazione della strategia terapeutica e nel successivo follow-up [3,4].…”
Section: Introductionunclassified